ANALYSIS OF CST (CASE, SUPPORT AND TREATMENT) AT H ABDUL MANAP HOSPITAL IN JAMBI CITY IN 2018 - Cici Lia Nopita; Mardiati Nadjib (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The CST clinic of H. Abdul Manap, the regional public hospital is the only type-C a hospital which provides ARV (Anti Retro Viral) treatment service in Jambi City. However, in the past five years, the trend of CST clinic utilization has tended to decrease. This research aims to analyze the factors affecting the decrease in the utilization of the CST clinic of H. Abdul Manap regional public hospital, Jambi City. Method: This study was used the qualitative method with purposive sampling technique. This research conducted in 37 participants were employed to obtain the primary data sources from observation and in-depth interviews with key informants. Those key informants included the management team (3 people), CST Clinic team (7 people), PLWHAs (18 people) and peer counselors (8 people) as well as FGDs (Focus Group Discussions). Results: The commitment of the concerned stakeholders, especially the chairman of the hospital and the CST team members in administering the CST service, has not been maximum. The budget allocation for CST clinic in the hospital was only for and limited to staff incentives. There had been no position for team leaders and case managers, while the doctors and staffs had not received any CST training. Some staffs even served double jobs. Conclusion: The service SOP, as well as the scheduled and continuous monitoring on SOP implementation and progress evaluation according to CST Clinic performance indicators, are required. The necessary of regional policies related to CST service, especially for the provision of CD4 reagents and tariffs; and the hospital director's decree to instruct not to refuse to treat PLWHA are also required. The Implication is a strong commitment from all stakeholders, especially the chairman of the hospital and the CST team members are required to improve the clinic utilization. Keywords: Analysis, Service System, CST Clinic